Reducing causes of inequity: policies focused on social determinants of health during generational transitions in Colombia - Juan Carlos Rivillas; Fabian Dario Colonia (Taylor & Francis Group, 2017)
Health inequalities often result from social inequities, and those, in turn, are generated by social determinants of health (SDoH). Hence, to reduce health inequalities, it is necessary to consider all health-related determinants. Disadvantages arise even before birth, and they tend to accumulate throughout an individual's life. Thus, policy actions intended to overcome these health inequalities should take place before birth and continue throughout life. This review aimed to describe the first steps of that Colombia has taken to reduce health inequalities during generational transitions through an inter-sectorial coordination upon SDoH. The review was guided by the question 'What are the implemented policy responses aimed to reduce health inequalities during generational transitions in Colombia, and what can be considered in order to improve inter-sectorial coordination?' Given the novelty of this area of research, the existent literature is presented more as narrative, rather than systematic review. Seven policies focused on five SDoH have been taken as examples. These policies show how Colombia plans to reduce health inequalities by acting upon these five SDoH: (1) early childhood development, (2) opportunities for education and first employment, (3) improved housing conditions, (4) social protection for families, and (5) vulnerable populations (e.g. elderly population). Additionally, more specific cases are examined in more detail that take place during sensitive periods in a person's life, such as pregnancy, birth, early childhood, entry to higher education, first time job search, family building, elderly years, and so on. The evidence represents Colombian's first steps toward reducing health inequalities during generational transitions. Elimination of health inequalities becomes feasible when governments recognize the importance of bringing opportunities to the worst-off populations, as well as the pivotal role of properly and well-coordinated inter-sectorial actions.